Marriage, Work, and the Dissolution of the Productive Household - Taylor, Luke (feminists@law, 2018)
The many figures that populated the family in the seventeenth and eighteenth centuries gradually disappeared until the couple of husband and wife took the centre of the stage, and the marriage contract became constitutive of domestic relations. - Carole Pateman, The Sexual Contract, p.116. This paper is an historical study of the dissolution of the productive household in (primarily) nineteenth-century English law and legal thought. Building on Pateman’s insights into the construction of the family and marriage in political thought, the paper shows how law and legal thought contributed to the disaggregation of work and family life, and constructed (in place of the household) a legal conception of the private family that revolved around the married couple. The first part of the paper traces the movement in scholarly legal thought from Blackstone’s “private oeconomical relations”, to the late nineteenth century category of “Domestic Relations”, and the eventual emergence of “Family Law” in the twentieth century. It identifies two key processes in this intellectual shift: the excision of master-servant law from the legal household and its (imperfect) identification with contract; and a concomitant move away from a contractual treatment of marriage towards a modern, specifically legal, status-based conception of the relation. The second part of the paper considers how institutional lawmaking and social norms combined to disaggregate the household in distinctly gendered ways. Addressing enclosure laws, family wage ideology, married women’s property laws, and judicial reinforcement of women’s presumed domesticity in breach of promise to marry cases, it shows how law and ideology reinforced the sexual contract by splitting the household along corresponding female/male and family/work lines.